Recognition of uppercase handwritten characters using multiple neural networks - 278228 Zyad Shaaban; Ghazali Sulong, 1958-; Duin, R. P. W.; International Conference on Robotics, Vision and Parallel Processing for Industrial Automation (1996 : USM, Perak)
59